New molecular approches using AR, FOXA1 and HER2 for outcome classification of estrogen Receptor-Positive (ER+) breast cancers” (2018)
Here, we studied new prognostic and predictive easy access strategies in breast cancer (molecular markers), for better classify ER+ breast cancer disease, which might provide additional information and be complementary to the clasical clinical-pathological prediction models.